Histological Transformation to Small Cell Carcinoma of an Adenosquamous Carcinoma of the Lung With Epidermal Growth Factor Receptor Mutation in Exons 20 and 21 After Treatment With Erlotinib: Case Report. Issue 13 (August 2019) - Fernández-Trujillo, Liliana; Tapia, Laura; Vallejo, Marcela; Aguirre, Marisol; Lores, Juliana; Sua, Luz F
Lung carcinoma currently represents 1 of the leading causes of death from cancer worldwide and regionally. The molecular identification of sensitive mutations of targeted treatment have changed the strategies of pharmacologic management in non-small cell lung carcinoma. However, mechanisms of resistance have been described, among them the change of histological type to small cell carcinoma. We present the case of a 46-year-old male patient, non-smoker, with a clinical history of a mass in the upper lobe of the right lung and an initial histological diagnosis of adenosquamous carcinoma of the lung, with the presence of mutations for epidermal growth factor receptor (EGFR) in exons 20 (S768I) and 21 (L858R). He received treatment with tyrosine kinase inhibitor (Erlotinib) with good clinical and radiological response. However, 1 year after the start of the medication, he consulted for a progressive onset of constitutional symptoms and respiratory symptoms, with radiographic worsening and new biopsy with a diagnosis of adenosquamous carcinoma with the adenocarcinoma component transformed to small cell carcinoma, with persistence of EGFR mutation. We describe the clinical, radiological, and laboratory characteristics as well as the outcome of this case. To conclude, among the mechanisms of resistance described to the treatment with tyrosine kinase inhibitors in patients with carcinomas with mutated EGFR, the transformation to small cell carcinoma besides being infrequent is particular, requiring a different diagnostic and therapeutic approach.